Pemikiran Syekh Muhammad Arsyad Al-Banjari tentang Zakat dalam Kitab Sabîl al-Muhtadîn Analisis Intertekstual - Muslich Shabir (Balai Penelitian dan Pengembangan Agama Semarang, 2009)
Sabil al-Muhtadin is a fiqh book written by Muhammadd Arsyad al-Banjari (d. 1812) in year 1193-1995 H / 1779-1781 A.D. Backgrounds of its written are, for example, desires to improve currently available Malay fiqh book entitled ash-Shirath al-Mustaqim written by Syekh Nuruddin Ar-Raniri. There are three significant thoughts on almsgiving / zakat described in Sabil al-Muhtadin, which are not explained in ash-Shirath al-Mustaqim. First, there are no obligation to almsgivingonjewelries except gold and silver jewelry. Second, portion of the needy are allowed to be utilized for production interests. Third, involvement of imam (leader) in managing zakat / almsgiving especially in giving zakat / almsgiving to the needy for productive interests. Those thoughts are evaluated by research team of IAIN Antasari Banjarmasin and Rasyidah HA as the result of Al-Banjari’s individual interpretation and judment (ijtihad). Al-Banjari in his preface of Sabil al-Muhtadin described that during his writting of this book, he based on books written by muta'akkhirin scholars in Syafi’i mazhab in particular al-Anshari’s Fath al-Wahhab (d. 926), al-Haitami’s Tuhfat al-Muhtaj(d. 973), asy-Syarbini’s Mughni al-Muhtaj (d. 977) and ar-Ramli’s Nihayat al-Muhtaj (d. 1004). With the confession of Al-Banjari, it is necessary to do research using intertextual approach to find out whether those thoughts are the results of his individual interpretation and judgment (ijtihad). After reviewing all named references, it turnedout that what are evaluated as ijtihad results are already discussed by previous scholars.Key Words: The Needy, Productive almsgiving / Zakat, Intertextual, Ijtihad